Does LEED Certification Save Energy? Evidence from Federal Buildings - Karen Clay; Edson R. Severnini; Xiaochen Sun (Institute of Labor Economics (IZA), 2021)
In the absence of first-best climate policy, energy efficiency has figured prominently among strategies to reduce carbon emissions. One of the most sought-after green certification in the building sector is the internationally recognized Leadership in Energy & Environmental Design (LEED). This paper examines the effects of LEED certification on energy efficiency in federally owned buildings. Using propensity score matching and difference in differences models, we find no effect of LEED certification on average energy consumption. This reflects the fact that energy use is one of a number of attributes that receives scores under the LEED program. Buildings with above average energy scores have greater energy efficiency post-certification. Some other attributes, notably higher water scores, decrease energy efficiency post-certification. Trade-offs across LEED attributes account for the absence of energy savings on average. If energy efficiency is the primary policy goal, LEED certification may not be the most effective means to reach that goal.
Keywords: O31; Q41; Q48; Q52; 330; energy efficiency; LEED certification; energy savings; federal buildings; trade-off across LEED attributes